Indexing wages to inflation in the EU: Fiscal drag and benefit erosion effects - Chrysa Leventi; Alberto Mazzon; Fabrice Orlandi (European Commission, Joint Research Centre (JRC), 2024)
In 2022 inflation hit European economies in a severe way. To protect the purchasing power of households, EU Member States adopted a series of exceptional fiscal policy measures. In this paper, we turn our focus on wage indexation, a policy option that has been relatively less explored in the relevant literature. The objective of the research is to analyse the (first-order) fiscal and distributional impact of wage indexation and of its two main subsequent effects, fiscal drag and benefit erosion. Using EUROMOD, the tax-benefit microsimulation model for the EU, we construct three hypothetical scenarios with uniform/diversified inflation shocks and with/without compensation schemes for the income losses caused by benefit erosion. We find that the budgetary impact of wage indexation varies widely among European countries. Interestingly, we also observe that in most countries, the relative magnitude of fiscal drag and benefit erosion is not affected by the magnitude of the increase in employment income. Our estimates suggest that in almost half of the countries, fiscal drag and benefit erosion cause an implicit increase in government revenues sufficient to finance an indexation of benefits and pensions to the inflation of that year. The latter would be associated with a substantial decrease in income inequality in the vast majority of EU Member States. Finally, we discuss how the existing automatic indexation adjustments embedded in EU countries' personal income tax schedules affect the magnitude and distributional implications of fiscal drag.
Keywords: 330